Enhancing University Students’ Soft Skills Through Character-Based Leadership Training - munzir (Jurnal Pengabdian Pemersatu Bangsa, 2026)
This community service activity aimed to improve students’ soft skills through character-based leadership training. The main problems faced by students include low communication skills, teamwork, public speaking abilities, and leadership competencies needed to face workplace challenges. The implementation method used a participatory approach through interactive lectures, group discussions, leadership simulations, public speaking training, and character value reflection. The activity was conducted over two days involving 35 students from various study programs. Evaluation was carried out using pretests, posttests, observations, and participant satisfaction questionnaires. The results showed significant improvement in leadership, effective communication, teamwork, problem-solving, and public speaking skills. The average participant score increased from 64.8 in the pretest to 84.4 in the posttest. In addition, participants demonstrated increased self-confidence, collaboration skills, and active participation during the training process. Participant satisfaction with the activity was categorized as very good. Therefore, character-based leadership training is effective in improving students’ soft skills and can be used as a strategy for character development in higher education.